2019
DOI: 10.1017/s0021932019000300
|View full text |Cite
|
Sign up to set email alerts
|

Early menarche and its relationship to paternal migrant work among middle-school-aged students in China

Abstract: Associations have been shown between father’s absence and menarcheal age, but most studies have focused on absence resulting from divorce, abandonment or death. Little research has been conducted to evaluate the effect on menarcheal age of paternal absence through migrant work. In a sample of 400 middle school students, this study examined the association between paternal migrant work and menarcheal age against a backdrop of extensive rural-to-urban migration in China. Data were collected through a self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…One study found that the first five years of life were the most critical for paternal influence to be protective against early menarche [104]. Another study found that it was not paternal absence, but the lack of a quality relationship with one's father that was linked with early menarche [106]. Depression, early childhood paternal absence, and early age at menarche were related to each other in another study [105].…”
Section: Disease Causes and Consequencesmentioning
confidence: 97%
See 1 more Smart Citation
“…One study found that the first five years of life were the most critical for paternal influence to be protective against early menarche [104]. Another study found that it was not paternal absence, but the lack of a quality relationship with one's father that was linked with early menarche [106]. Depression, early childhood paternal absence, and early age at menarche were related to each other in another study [105].…”
Section: Disease Causes and Consequencesmentioning
confidence: 97%
“…Lack of paternal influence and quality of the paternal relationship during early childhood has been linked with early menarche [102][103][104][105][106]. One study found that the first five years of life were the most critical for paternal influence to be protective against early menarche [104].…”
Section: Disease Causes and Consequencesmentioning
confidence: 99%